Long-circulating XTEN864-annexin A5 fusion protein for phosphatidylserine-related therapeutic applications - Haeckel, Akvile; Ascher, Lena; Beindorff, Nicola; Prasad, Sonal; Garczynska, Karolina; Guo, Jing; Schellenberger, Eyk (Apoptosis, 2021)
Annexin A5 (anxA5) is a marker for apoptosis, but has also therapeutic potential in cardiovascular diseases, cancer, and, due to apoptotic mimicry, against dangerous viruses, which is limited by the short blood circulation. An 864-amino-acid XTEN polypeptide was fused to anxA5. XTEN864-anxA5 was expressed in Escherichia coli and purified using XTEN as tag. XTEN864-anxA5 was coupled with DTPA and indium-111. After intravenous or subcutaneous injection of 111In-XTEN864-anxA5, mouse blood samples were collected for blood half-life determination and organ samples for biodistribution using a gamma counter. XTEN864-anxA5 was labeled with 6S-IDCC to confirm binding to apoptotic cells using flow cytometry. To demonstrate targeting of atherosclerotic plaques, XTEN864-anxA5 was labeled with MeCAT(Ho) and administered intravenously to atherosclerotic ApoE−/− mice. MeCAT(Ho)-XTEN864-anxA5 was detected together with MeCAT(Tm)-MAC-2 macrophage antibodies by imaging mass cytometry (CyTOF) of aortic root sections. The ability of anxA5 to bind apoptotic cells was not affected by XTEN864. The blood half-life of XTEN864-anxA5 was 13 h in mice after IV injection, markedly longer than the 7-min half-life of anxA5. 96 h after injection, highest amounts of XTEN864-anxA5 were found in liver, spleen, and kidney. XTEN864-anxA5 was found to target the adventitia adjacent to atherosclerotic plaques. XTEN864-anxA5 is a long-circulating fusion protein that can be efficiently produced in E. coli and potentially circulates in humans for several days, making it a promising therapeutic drug.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Apoptotic mimicry; Atherosclerosis; Cancer; Inflammation; Inflammatory cytokine storm; Programmed cell death